2008
DOI: 10.1152/ajpendo.90536.2008
|View full text |Cite
|
Sign up to set email alerts
|

Functional impact of high protein intake on healthy elderly people

Abstract: Decline in muscle mass, protein synthesis, and mitochondrial function occurs with age, and amino acids are reported to enhance both muscle protein synthesis and mitochondrial function. It is unclear whether increasing dietary protein intake corrects postabsorptive muscle changes in aging. We determined whether a 10-day diet of high [HP; 3.0 g protein ⅐ kg fat-free mass (FFM) Ϫ1 ⅐ day Ϫ1 ] vs. usual protein intake (UP; 1.5 g protein ⅐ kg FFM Ϫ1 ⅐ day Ϫ1 ) favorably affects mitochondrial function, protein meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 54 publications
6
82
1
2
Order By: Relevance
“…They conclude that ingesting more than 30 g protein at a single meal may be an inefficient means of stimulating muscle protein synthesis. This is in agreement with a recent study that showed no benefit of very large amounts of protein for 10 days (3.0 vs. 1.5 g/kg) in terms of muscle protein synthesis [24].…”
Section: Protein and Amino Acidssupporting
confidence: 93%
“…They conclude that ingesting more than 30 g protein at a single meal may be an inefficient means of stimulating muscle protein synthesis. This is in agreement with a recent study that showed no benefit of very large amounts of protein for 10 days (3.0 vs. 1.5 g/kg) in terms of muscle protein synthesis [24].…”
Section: Protein and Amino Acidssupporting
confidence: 93%
“…Moreover, a recent systematic review and meta-analysis of 20 randomized controlled trials investigating dietary approaches in the management of type 2 diabetes indicated that high-protein diets are among the few approaches that are effective in improving glycemic control (Ajala et al, 2013). Several studies have reported stimulation of muscle protein synthesis with generous protein intakes with and without exercise in elderly individuals (Cermak et al, 2012;Candow et al, 2006;Esmarck et al, 2001;Symons et al, 2007;Verdijk et al, 2009;Walrand et al, 2008). Notwithstanding, the combined metabolic abnormalities associated with old age, obesity, and type 2 diabetes pose specific therapeutic challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Acute exercise induces activation of BCKD complex in human skeletal muscle, but after training the activity of this enzyme is reduced, along with an increase in BCKD kinase protein (Howarth et al 2007). In a small randomized crossover study, the activity of BCAT and BCKD complex in skeletal muscle has been found similar in young and elderly healthy persons and there was no difference in the activity of these enzymes during shortterm ingestion of a high-protein diet compared with usual protein dietary content (Walrand et al 2008).…”
Section: Leucinementioning
confidence: 96%